Radio Republik Indonesia Surakarta, 1945-1960s: Its Role in Efforts to Maintain Indonesian Independence and the Formation of National Culture - Dhanang Respati Puguh (Indonesian Historical Studies, 2017)
This article discusses the role of Radio Republik Indonesia (RRI, The Radio of Republic of Indonesia) Surakarta in the period 1945-1960s. In that period RRI Surakarta had two roles in the context of decolonization. In the period 1945-1949, RRI Surakarta had a role in the effort to maintain the independence of Indonesia. The RRI Surakarta employees struggled to maintain the existence of RRI Surakarta with rescuing the station and transmitter so that the struggle of the Indonesian nation in defending the independence of Indonesia could be broadcasted to various parts. In the period 1950-1960s RRI Surakarta participated in efforts to the formation a national culture. When the discourse of national culture continued to be discussed by the elite of Indonesia, the Bureau of the Radio of the Republic of Indonesia had the establishment and set choice of ways to build a national culture since 1950. In this connection, RRI should be directed to build a national culture. Based on the policy of the Bureau of Radio of the Republic of Indonesia, RRI Surakarta realized that idea by organizing Javanese art broadcasts (gamelan, wayang wong, kethoprak, and shadow puppets), “local entertainment” and national music, and organizing Radio Star Competition. RRI Surakarta Radio Star made an important role in the creation of popular music in Indonesia.